Need for pacemaker implantation in patients with normal QRS duration immediately after transcatheter aortic valve implantation. Issue 12 (3rd October 2019) - Schoechlin, Simon; Jalil, Fares; Blum, Thomas; Ruile, Philipp; Hein, Manuel; Nührenberg, Thomas G; Arentz, Thomas; Neumann, Franz-Josef
Abstract: Aims: We sought to assess the need for permanent pacemaker implantation (PPI) in patients with QRS <120 ms in electrocardiogram (ECG) after transcatheter aortic valve implantation (TAVI). Methods and results: We retrospectively analysed 1139 consecutive patients who underwent transfemoral TAVI between 2008 and 2016, receiving different valve types. All patients were surveyed by continuous ECG monitoring for 48 h, 12-lead ECGs starting immediately after procedure, as well as 24-h Holter recording the day before discharge. Indication for PPI was at the discretion of the attending physician. Among 760 patients with QRS <120 ms prior to the TAVI procedure, 400 patients showed QRS <120 ms immediately after procedure, whereas 360 patients had QRS ≥120 ms. In the group with QRS <120 ms, PPI was performed in 34 patients [8.5%; 95% confidence interval (CI) 5.6–11.2%] during the first week. Eight of the PPIs in the group with QRS <120 ms (2%; CI 0.8–3.5%) fulfilled Class I indications for PPI after TAVI, whereas 26 PPIs had different indications [left bundle branch block, sick sinus, low-grade atrioventricular (AV) block]. Complete AV block developed in three patients of the group of QRS <120 ms (0.75%; CI 0.0–1.7%), which in all cases occurred after the 48 h-surveillance period. During 1-year follow-up, 11 PPIs were performed (2.8%; CI 1.2–4.5%), thereof three PPI for Class I indications including one complete AV block. Conclusion: In patients with QRS duration <120 ms immediately after TAVI, the risk for complete AV block was low during the first week after TAVI and 1-year follow-up.